Durable Goods in the Extended Linear Expenditure System - Dixon, Peter B.; Lluch, Constantino (Review of Economic Studies, 1977)
Peter B. Dixon, Constantino Lluch; Durable Goods in the Extended Linear Expenditure System, The Review of Economic Studies, Volume 44, Issue 2, 1 June 1977, Pag